Equivalence of the Steady State Concentrations of Two Dosage Regimen of Phenytoin Using Computer Optimisation Programme OPT6 - S Bhuvaneshwari, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Equivalence of the Steady State Concentrations of Two Dosage Regimen of Phenytoin Using Computer Optimisation Programme OPT6